Strategic Questions #2: Has Man a Function in Universe? (Book Works, London; Eastside Projects, Birmingham; Eastside Projects, Birmingham, 2008)
This book is the sixth in a series of co-publishing partnerships, entitled Fabrications, initiated by Book Works. Strategic questions is an ongoing project begun in 2002 to develop 40 projects in response to 40 questions written by Buckminster Fuller. Has Man a Function in Universe? is the 23rd in the series.
English
Keywords: N7560-8266 Visual Arts. Special subjects of art